Herman Melville's use of animals: the chain of natural science, anthropomorphic symbolism, and literary naturalism in Moby-Dick and "The Encantadas" - Lamberson, John Gregory, author; Furrh, Douglass Madison, advisor; Taylor, Cynthia, committee member; Vanden Heuvel, Brian, committee member (Colorado State University. Libraries, 2013)
In Moby-Dick and "The Encantadas," Herman Melville's narrators often assume the role of a naturalist, in the mode of natural history. Beginning with careful and realistic explication, Melville understands different animals in terms of their physical characteristics and behavior, in a manner influenced by Charles Darwin. After establishing an accurate picture, he proceeds to take the animals and transform them to concepts related to literary naturalism in a process of anthropomorphic symbolism. Melville's ambiguous stance on animal awareness and pain further clarifies his project of using animals to be representative of mostly human concepts. Moby-Dick and "The Encantadas" illustrate this chain with Melville's naturalistic treatment of whales and tortoises, respectively. With the precision of a scientist and the spirit of an artist, Melville uses animals as symbols of concepts that anticipate literary naturalism, most notably determinism. Melville's utilization of natural science as a means to symbolism made him a precursor to literary naturalism, which itself grew out of the influence of Darwinian ideas.
Keywords: literary naturalism; Darwin; encantadas; Melville; Moby-Dick; natural science